Analysis of Genetic Diversity in Tea Plant Population and Construction of DNA Fingerprint Profile Using SNP Markers Identified by SLAF-Seq - Yiding Liu; Yanqi Teng; Jie Zheng; Aziz Khan; Xiang Li; Yang Tian; Junlin Cui; Qigao Guo (Horticulturae)
The analysis and identification of the genetic diversity of plant germplasm resources and varieties are crucial for plant breeding. DNA fingerprinting using genomic molecular markers is crucial for precisely identifying germplasm resources. In this study, the SLAF-seq was performed using 47 germplasm resources of the Wanzhou tea plant population and 5 common cultivated varieties from the Yunnan, Sichuan, and Fujian provinces. A total of 7,447,940 SNPs were identified from 1,641,569 SLAF tags with an averaged sequencing depth of 11.73 (Q30 94.93% and GC 41.37%), which were used to analyze the population composition and genetic diversity. Results showed a large degree of genetic diversity and genetic variation among the samples. The cluster analysis showed that the tea plant population was categorized into three groups, indicating that these germplasms could not be fully classified by their geographical origin, and the linkage disequilibrium analysis indicates that the population resources of the XJ production area are more modern in evolution. A total of 371 uniformly distributed SNP loci were selected and successfully employed to construct the first SNP fingerprint and quick response code (QR code) for tea resources in Wanzhou. These findings offer new insights for genotyping, classifying, and identifying germplasm and genetic resources in the breeding of the Wanzhou tea population.